2019
DOI: 10.1186/s13756-019-0581-8
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of peripheral intravenous catheter failure among inpatients: variability between microbiological data and clinical signs and symptoms

Abstract: Background Peripheral intravenous catheters (PIVCs) are the most widely used invasive devices among inpatients. Catheter-related bloodstream infections (CRBSI) are serious yet preventable events for patients. Although the contribution of PIVCs towards these infections is gradually being recognised, its role in the Spanish setting is yet to be determined. We aimed to estimate the rate and incidence of PIVC failure at Manacor hospital (Spain) as baseline within a wider quality improvement initiative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 37 publications
0
27
1
2
Order By: Relevance
“…These results provide insight into the various mechanisms that lead to PIVC failure, reflecting a poor adherence to recommendations with associated iatrogenic harms to patients [35]. PIVC failure triggers the need for a new PIVC insertion with its potential adverse events, increasing the risk of CRBSIs [4], as well as imposing a significant demand on healthcare resources [36,37]. We observed suboptimal performance between different hospital environments and types regarding the clinical outcomes from CPG recommendations for care of PIVC.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…These results provide insight into the various mechanisms that lead to PIVC failure, reflecting a poor adherence to recommendations with associated iatrogenic harms to patients [35]. PIVC failure triggers the need for a new PIVC insertion with its potential adverse events, increasing the risk of CRBSIs [4], as well as imposing a significant demand on healthcare resources [36,37]. We observed suboptimal performance between different hospital environments and types regarding the clinical outcomes from CPG recommendations for care of PIVC.…”
Section: Discussionmentioning
confidence: 85%
“…In our study, we observed that approximately 45% of PIVC insertion sites were not visible, a disappointing scenario considering the impact that inspection of the PIVC insertion site per shift would have to prevent and mitigate adverse events [ 31 ]. Removal of the PIVC should occur if phlebitis, inflammation or obstruction are present, or intravenous therapy has completed in the previous 24 hours, or the PIVC is no longer needed [ 4 , 23 , 34 ]. However, 9% of total PIVCs were unnecessarily maintained, with no differences between these outcomes and the hospital environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PIVC failure triggers the need for a new PIVC insertion with its potential adverse events, increasing the risk of CRBSIs [4], as well as imposing a significant demand on healthcare resources [36,37]. We observed suboptimal performance between different hospital environments and types regarding the clinical outcomes from CPG recommendations for care of PIVC.…”
Section: Characteristics Of the Contextmentioning
confidence: 85%
“… 13 Current SPC practice has seen a shift from routine replacement every 72 hours to replacement when clinically indicated. 14 The reported incidence rate of complications in patients undergoing catheter insertion is up to 42%. 15 The most common complications include phlebitis, occlusion, infiltration and extravasation, and catheter-related bloodstream infection (CR-BSI).…”
Section: Complicationsmentioning
confidence: 99%